1986
DOI: 10.1128/jb.167.2.496-502.1986
|View full text |Cite
|
Sign up to set email alerts
|

Release of cell-free ice nuclei by Erwinia herbicola

Abstract: Several ice-nucleating bacterial strains, including Erwinia herbicola, Pseudomonas fluorescens, and Pseudomonas syringae isolates, were examined for their ability to shed ice nuclei into the growth medium. Only E. herbicola isolates shed cell-free ice nuclei active at -2 to -10°C. These cell-free nuclei exhibited a freezing spectrum similar to that of ice nuclei found on whole cells, both above and below -5°C. Partially purified cell-free nuclei were examined by density gradient centrifugation, chemical and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0
4

Year Published

1989
1989
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(85 citation statements)
references
References 31 publications
(41 reference statements)
6
75
0
4
Order By: Relevance
“…Indeed, previous estimates of the numbers of live ice-nucleating bacteria in soils have been unable to account for observed ice active site densities (Conen et al, 2011). Non-viable cells, cell membrane fragments and membrane vesicles have all been shown in the laboratory to exhibit IN activity (Maki and Willoughby, 1978;Phelps et al, 1986;Hartmann et al, 2013;Augustin et al, 2013), and dead bacteria have been postulated to contribute significantly to the ice-nucleating ability associated with plant tissues (Ashworth and Kieft, 1995;Lindow, 1983a, b). While the lifetime of IN active proteins derived from bacteria and fungi in soils is unknown, there is evidence to suggest that certain proteins in soils can have extremely long residence times, on the order of centuries (Amelung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, previous estimates of the numbers of live ice-nucleating bacteria in soils have been unable to account for observed ice active site densities (Conen et al, 2011). Non-viable cells, cell membrane fragments and membrane vesicles have all been shown in the laboratory to exhibit IN activity (Maki and Willoughby, 1978;Phelps et al, 1986;Hartmann et al, 2013;Augustin et al, 2013), and dead bacteria have been postulated to contribute significantly to the ice-nucleating ability associated with plant tissues (Ashworth and Kieft, 1995;Lindow, 1983a, b). While the lifetime of IN active proteins derived from bacteria and fungi in soils is unknown, there is evidence to suggest that certain proteins in soils can have extremely long residence times, on the order of centuries (Amelung et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies have shown that the variability of nucleating frequencies is a function of seasonal and diurnal changes for some bacterial populations (Hirano and Upper, 1989). The dead and even the cell-free nuclei of some kinds of bacteria exhibited freezing properties (Anderson and Ashworth, 1986;Phelps et al, 1986). Cochet et al (1994) also have shown that pH negatively influences the bacterial nucleation activity.…”
Section: Introductionmentioning
confidence: 99%
“…Although shedding of ECINs was quite variable in quantity, usually 10 to 30% of the INA at Ϫ4°C was associated with ECINs when E. herbicola cells were grown on YE medium at 20°C (data not shown). Phelps et al (1986) reported that an average of 10% of the total ice nuclei from E. herbicola M1 were cell-free and active at Ϫ3°C when grown on a minimal glycerol medium at 15°C.…”
Section: Association Of Ina With Ecins and Whole Cellsmentioning
confidence: 99%